How can educational research support practice at scale? Attending to educational designer needs. (4th October 2018) - McKenney, Susan; Schunn, Christian D.
Abstract : Curricula, assessments and teacher professional development programmes wield a powerful influence on teaching and learning enactment. Together with the interpretation of those using them, these products mediate the flow of ideas from research to practice. In most countries, those curricula, assessments and professional development programmes that become widely used are created by educational designers. Given their crucial function, it is surprising that the role of educational designers is rarely recognised in the educational research literature, studied empirically or supported in practice. This article argues that educational research stands to (better) support practice at scale when it is attuned to the needs of educational designers. First, mechanisms for knowledge production and use are discussed, including the linkage role played by educational designers in the educational infrastructure of most countries. Then, the importance of understanding and bolstering the linkage between research findings and the work of designers is discussed. Arguments are given for research to better support those who design for scale, along with sample research questions posed by educational designers. In these, a distinction is made between the knowledge designers crave to shape their products (curricula, assessments, teacher professional development) and the knowledge they need to shape the processes through which those products come to fruition. This article closes with a call for educational researchers to explicitly focus their knowledge creation and dissemination efforts towards research consumers with the largest direct effects on teaching and learning: educational designers.